A Study on the Improvement of College Students’ Psychological Pressure and Anxiety by Using English Psychological Script Activities - Mu, Lina; Du, Baiyan; Hou, Xuemei (Frontiers in Psychology, 2022)
This study conducted an experiment of English script activities on 279 senior students from two universities in Guangdong Province, China. The purpose of this study was to explore the effect of English psychological script activities on improving the psychological pressure and anxiety of college students. The results show that, firstly, before the experiment, the overall psychological pressure and anxiety of college students are at a medium high level. The gender difference shows that the psychological pressure and anxiety level of girls are higher than that of boys. The professional difference shows that the psychological pressure and anxiety level of Humanities and social sciences majors are higher than that of science and engineering majors. After the experiment, the overall psychological pressure and anxiety level of college students have a significant improvement effect. From the overall level, English psychological script has the highest impact on evaluation anxiety and test anxiety. From the perspective of gender differences, English psychological scripts have the highest effect on improving the evaluation anxiety of boys, and the effect of improving test anxiety and evaluation anxiety of girls is the highest. From the perspective of professional differences, English psychological scripts have an average impact on the psychological pressure and anxiety of students majoring in Humanities and Social Sciences, while they have the highest impact on the interpersonal stress of students majoring in science and technology. The results of this research provide more reference value for college students' English education and mental health improvement.